Co-utilization of quarry tailings and fly ash for non-sintered ultra-lightweight aggregates (ULWAs) by autoclave technology. (5th September 2022) - Wang, Shunfeng; Yu, Long; Yang, Fei; Zhang, Weikang; Xu, Linglin; Wu, Kai; Tang, Luping; Yang, Zhenghong
Highlights: Using solid wastes (fly ash and quarry tailings) to prepare the non-sintered ULWAs by autoclave technology. Adding the physical and chemical foaming agents into LWAs to increase the total porosity of ULWAs. The pore structure of ULWAs was tested by MIP and NMR. Abstract: Quarry tailings as solid waste with large output bring a heavy environmental and economic burden. The main objective of this study is to investigate the feasibility of co-utilizing quarry tailings and fly ash (FA) as the main sources in preparing the lightweight aggregates (LWAs). The expand perlite powder (characterized with low density and high surface area) and two chemical foaming agents (ammonium carbonate and Al powder) was added to reduce the density of LWAs furtherly and fabricate a type of ultra-lightweight aggregates (ULWAs) through autoclave curing. In spite of the basic properties (compressive strength, 1 h of water absorption, loose bulk density and apparent particle density), the evolution of pore structures in relation to the type of foaming agents were also determined by combining scanning electron microscope (SEM), mercury intrusion porosimetry (MIP) and Nuclear Magnetic Resonance (NMR). The results show that increasing the expand perlite content could increases the compressive strength and water absorption, decreases the loose bulk density, apparent density and the total porosity. The pores wall gradually reduces with the increase of chemical foaming agents. Isolated pores will transform into connected pores, which also increase the most probable pore diameter and total porosity. The loose bulk density of specimens with 3 wt% (NH4 )2 CO3 and Al powder are 873 kg/m 3 and 798 kg/m 3 compared to blank (1132 kg/m 3 ). This work lays a solid foundation for the design and preparation of ULWAs from solid wastes.